2007
DOI: 10.1007/s12028-007-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal and Recurrent Subarachnoid Hemorrhage Due to an Herbal Supplement Containing Natural Coumarins

Abstract: We report a 53-year-old woman with spontaneous subarachnoid hemorrhage due to the use of an herbal supplement containing red clover, dong quai, and Siberian ginseng.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…Some reviews listed Red clover as having the potential to increase the risk of bleeding or potentiate the effects of warfarin, based on the fact that Red clover inhibited CYP2C9 and contained natural coumarins [107]. But there was only one case report support this statement A 53-year-old woman developed spontaneous subarachnoid hemorrhage when she was taking warfarin with herbal supplements containing Red clover, Chinese Angelica, Ginseng, and others for 4 months [108]. With this case reports, it is not possible to identify which, if any, of these constituents in the herbal supplements might have contribution to the hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
“…Some reviews listed Red clover as having the potential to increase the risk of bleeding or potentiate the effects of warfarin, based on the fact that Red clover inhibited CYP2C9 and contained natural coumarins [107]. But there was only one case report support this statement A 53-year-old woman developed spontaneous subarachnoid hemorrhage when she was taking warfarin with herbal supplements containing Red clover, Chinese Angelica, Ginseng, and others for 4 months [108]. With this case reports, it is not possible to identify which, if any, of these constituents in the herbal supplements might have contribution to the hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
“…These could include minor adverse events such as purpura 96 and gum bleeding 146 to major events such as cerebrocranial bleeding that led to death 114,149 . Herbs or dietary supplements that were reported to result in haemorrhage include: consumption of bilberry fruit, 60 cranberry juice, 83–86 ginger, 111 Ginkgo biloba, 114 Chinese wolfberry, 73,74 Japanese food, 124 PC‐SPES nutritional supplement, 140 pomegranate juice, 143 grapefruit juice, 121 red clover, 97 vitamin E, 40 St John's wort 152 and wormwood 166 as well as herbs such as Danshen, 93 Dong quai, 97 Devil's claw, 96 Quilingao, 146 Shengmai‐yin 149 and ginseng 97 . One case report also described an elderly individual who developed multiple haematoma after the application of a chamomile based skin lotion 67 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] To our knowledge, the only reported case of intracranial bleeding associated with herbal supplements is a nonaneurysmal subarachnoid hemorrhage in a patient taking Red Clover. [ 1 ] The mechanism underlying Red Clover induced coagulopathy is assumed to be due to the coumarin derivatives, hence, the contraindication for its use alongside warfarin; however, in-vitro evidence has shown that it also has negative effects on platelet activity through inhibition of platelet adhesion. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains only one case of intracranial bleeding due to Red Clover where a patient suffered a spontaneous, nonaneurysmal subarachnoid hemorrhage. [ 1 ] This case presents a female patient who suffered an acute-on-chronic SDH requiring craniotomy and repeat craniotomy for re-accumulation likely due to Red Clover consumption. It serves to raise awareness of the importance of inquiring about herbal compounds in drug history as a predictor of a patient's surgical bleeding risk.…”
Section: Introductionmentioning
confidence: 99%